Revolutionary Egypt in the Eyes of the Muslim Brotherhood: A Framing Analysis of Ikhwanweb, Mohammed el-Nawawy and Mohamad Hamas Elmasry (2018). (1st April 2020) - Al-Zo'by, Mazhar
Revolutionary Egypt in the Eyes of the Muslim Brotherhood: A Framing Analysis of Ikhwanweb, Mohammed el-Nawawy and Mohamad Hamas Elmasry (2018)Lanham, Boulder, New York and London: Rowman & Littlefield, 177 pp., ISBN 978-1-53810-072-1, h/bk, $75.00